Canine fossa puncture in endoscopic sinus surgery: report of two cases - Sireci,Federico (2017)
Abstract Introduction: Chronic rhinosinusitis with nasal polyposis is a common chronic disease that often affects maxillary sinus. Endoscopic sinus surgery is the most common procedure for treating the majority of maxillary sinus lesions. Objective: To demonstrate the role of canine fossa puncture during endoscopic sinus surgery procedure in patients with severe maxillary sinus disease. Methods: We present 2 cases where canine fossa puncture has been performed as method to obtain a complete access to the maxillary antrum. Results: According our experience, 2 cases on 296 endoscopic sinus surgery (0.6%) where antrostomy and used of angled microdebrider were not sufficient, canine fossa puncture has been performed as an alternative method to obtain a complete access to the maxillary antrum. Conclusion: Although the advent of endoscopic sinus surgery, our cases support the fact that actually canine fossa puncture is a minimally invasive technique useful in selected cases.